DI BALIK SENYUMAN: ANALISIS PERAN KOMUNIKASI NON-VERBAL DALAM MEMBANGUN RESILIENSI ANAK USIA PRA-SEKOLAH DI TENGAH KONFLIK KELUARGA - Sutrianingrum, Sutrianingrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This investigation explores the dimensions of wordless communication in the psychological resilience development process of preschool-aged children facing conflict dynamics within family systems through systematic literature review methodology. Exploration was conducted on 8 published scientific works spanning 2015-2025 by applying thematic analysis approaches reinforced with data triangulation to ensure finding credibility. Investigation results demonstrate that non-verbal interactions play a central role in resilience construction through pathways of emotional responsiveness, legitimation of children's subjective experiences, and cultivation of affective regulation capabilities. Democratic communication characteristics marked by optimal openness consistently demonstrate positive contributions to children's adaptive capacity in confronting adversity. Children's interpretation processes of non-verbal signals display sophisticated cognitive complexity, where coping strategies are developed based on ecosystem responsiveness quality. Family resilience functions as a moderator variable that amplifies non-verbal communication effectiveness in building individual adaptive capacity. Findings indicate that systematic non-verbal communication development strategies can generate sustained protective effects. This research contributes theoretically to elucidating complex mechanisms of resilience formation and provides practical implications for developing comprehensive family intervention programs. ABSTRAK Studi ini menginvestigasi dimensi komunikasi tanpa kata dalam proses membangun daya tahan psikologis anak usia prasekolah yang menghadapi dinamika konflik keluarga melalui metodologi tinjauan pustaka yang sistematis. Eksplorasi dilaksanakan terhadap 8 karya ilmiah terpublikasi dalam kurun waktu 2015-2025 dengan mengaplikasikan pendekatan analisis tematik yang diperkuat triangulasi data untuk menjamin kredibilitas temuan. Hasil investigasi memperlihatkan bahwa interaksi non-verbal memainkan peran sentral dalam konstruksi resiliensi melalui jalur responsivitas emosional, legitimasi pengalaman subjektif anak, dan pengembangan kemampuan regulasi afektif. Karakteristik komunikasi demokratis yang ditandai keterbukaan optimal secara konsisten mendemonstrasikan kontribusi positif terhadap kapasitas adaptif anak dalam menghadapi tantangan. Proses interpretasi anak terhadap sinyal non-verbal memperlihatkan kompleksitas kognitif yang rumit, dimana strategi koping dikembangkan berdasarkan kualitas responsivitas ekosistem. Resiliensi keluarga berfungsi sebagai variabel moderator yang memperkuat efektivitas komunikasi non-verbal dalam membangun kapasitas adaptif individual. Temuan mengindikasikan strategi pengembangan komunikasi non-verbal yang sistemik dapat menghasilkan efek protektif berkelanjutan. Penelitian ini berkontribusi secara teoretis dalam menguraikan mekanisme kompleks pembentukan resiliensi dan memberikan implikasi praktis bagi pengembangan program intervensi keluarga komprehensif.